2011
DOI: 10.1369/0022155411430095
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of the Glutamate Transporter GLT-1 in Pancreas

Abstract: SummaryThe glutamate uptake transporter GLT-1 is best understood for its critical role in preventing brain seizures. Increasing evidence argues that GLT-1 also modulates, and is modulated by, metabolic processes that influence glucose homeostasis. To investigate further the potential role of GLT-1 in these regards, the authors examined GLT-1 expression in pancreas and found that mature multimeric GLT-1 protein is stably expressed in the pancreas of wild-type, but not GLT-1 knockout, mice. There are three prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
5
8
0
Order By: Relevance
“…GLT-1 is expressed at low levels in the pancreas [65], thereby raising the question whether some aspects of GLT-1 function might be related to pancreatic GLT-1 endocrine and/or exocrine activity. However, recent studies using mice with a brain-specific GLT-1 deficiency demonstrate that GLT-1 loss in the brain alone is sufficient to account for the primary phenotypes associated with total systemic GLT-1 loss [1, 66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLT-1 is expressed at low levels in the pancreas [65], thereby raising the question whether some aspects of GLT-1 function might be related to pancreatic GLT-1 endocrine and/or exocrine activity. However, recent studies using mice with a brain-specific GLT-1 deficiency demonstrate that GLT-1 loss in the brain alone is sufficient to account for the primary phenotypes associated with total systemic GLT-1 loss [1, 66].…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with reduced brain IDE activity, GLT-1 loss also caused a marked increase in IDE activity in the liver, which expresses high levels of GLT-1 in zone 3 hepatocytes [65, 72]. While we found a significant increase in the ratio of Aβ 42 /Aβ 40 in these mice at 6 months of age, we did not find any other significant changes in Aβ accumulation between the GLT wt /AβPP/PS1 and GLT het /AβPP/PS1 groups at either 6 or 9 months [20].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue lysates for western blot analyses were then prepared as previously described [22] with the following minor modifications: phosphatase inhibitor cocktail sets 2 and 3 (Sigma, St. Louis, MO) were added (10 μ/ml) to the lysis buffer and tissues were homogenized twice by hand using an Eppendorf tube-fitting pestle (Eppendorf, Hauppauge, NY) before centrifuge clarification. Criterion 4–20% TGX gels (Bio-Rad, Hercules, CA) were loaded with 20 μg/lane and probed only once after overnight incubation (4 C) with the following antibodies: AT8, AT100, AT270 (from Thermo Scientific, Waltham, MA); Tau-5, TauC3, anti-phospho-tau 396 (from Life Technologies, Grand Island, NY); CP13, and PHF-1 (gifts from Peter Davies); rabbit polyclonal pan-tau antibodies (gift from Virginia Lee); SOD2, AβPP, and GFAP (from EMD Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
“…However, as * This work was supported by the Norwegian Research Council (Centre of summarized in Table 1, there is a great deal of uncertainty. Some investigators have reported expression in the plasma membranes but have arrived at different conclusions with respect to cell types and functional roles (10,(22)(23)(24)(25). Another study (26) proposed a radically new model in which EAAT2 colocalizes with the VGLUT3 in the membranes of insulincontaining secretory granules.…”
mentioning
confidence: 99%